2022
DOI: 10.3389/fimmu.2022.843322
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Profiling Reveals Heterogeneity of Primary and Lymph Node Metastatic Tumors and Immune Cell Populations and Discovers Important Prognostic Significance of CCDC43 in Oral Squamous Cell Carcinoma

Abstract: Although substantial progress has been made in biological research and clinical treatment in recent years, the clinical prognosis of oral squamous cell carcinoma (OSCC) is still not satisfactory. Tumor immune microenvironment (TIME) is a potential target, which plays an essential role in the response of anti-tumor immunity and immunotherapy. In this study, we used scRNA-seq data, revealing the heterogeneity of TIME between metastatic and primary site. We found that in the metastatic site, the content of cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Related study found that CAFs in HNSCC mainly comprise myCAFs that play key roles in HNSCC progression, including matrix remodeling, the production of growth factors and cytokines, and metabolic effects [60]. CXCL12 is a vital chemokine, which can promote cancer cells proliferation, angiogenesis, and metastasis [61], and Wang et al found that CXCL12 is mainly secreted by iCAFs in OSCC [59]. That means iCAFs may facilitate HNSCC progression via some mechanisms.…”
Section: Biological Heterogeneity Of Cafs In Hnsccmentioning
confidence: 99%
See 1 more Smart Citation
“…Related study found that CAFs in HNSCC mainly comprise myCAFs that play key roles in HNSCC progression, including matrix remodeling, the production of growth factors and cytokines, and metabolic effects [60]. CXCL12 is a vital chemokine, which can promote cancer cells proliferation, angiogenesis, and metastasis [61], and Wang et al found that CXCL12 is mainly secreted by iCAFs in OSCC [59]. That means iCAFs may facilitate HNSCC progression via some mechanisms.…”
Section: Biological Heterogeneity Of Cafs In Hnsccmentioning
confidence: 99%
“…The roles of CAFs are as varied as their identification markers, and they have dynamically heterogeneous impacts on cancer at various stages [54][55][56].According recent research, CAFs were divided into "myofibroblastic CAFs" (myCAFs), "inflammatory CAFs" (iCAFs)and "antigen-presenting CAFs" (apCAFs) according to their characteristic marker genes, and these CAFs subclusters showed distinct phenotypes enriched in myofibroblast function, ECM remodeling and antigen-presenting function respectively [57][58][59]. Among them, myCAFs are characterized by myofibroblasts with high α-SMA expression and enrichment in smooth muscle contraction [57], and ECM-receptor interaction, vascular smooth muscle contraction, and focal adhesion are enriched in myCAFs [59]. Related study found that CAFs in HNSCC mainly comprise myCAFs that play key roles in HNSCC progression, including matrix remodeling, the production of growth factors and cytokines, and metabolic effects [60].…”
Section: Biological Heterogeneity Of Cafs In Hnsccmentioning
confidence: 99%
“…Clustering identi ed differentially expressed genes for clusters utilizing the Wilcoxon Rank Sum test, with absolute log2 fold change (FC) ≥ 0.5 and a minimum cell population fraction of 0.3 in either of the two populations. The R package SingleR (version 2.2.0) was then used to further annotate single cells by leveraging reference transcriptomic datasets of pure cell types to infer the cell of origin of each single cell independently, while manually con rming the cell types using known canonical cell markers from previous studies [23]. Table 2 provides information about the biomarkers.…”
Section: Cell Class Labelingmentioning
confidence: 99%
“…Single-cell RNA sequencing is an innovative technique for sequencing the transcriptome of a single cell as a speci c research object and performing bioinformatics statistical analysis of the resulting data [22]. Using conventional technologies such as micro uidics and barcode labeling, numerous cells can be promptly and e ciently labeled, sequenced, and analyzed, and the analysis software can easily capture gene expression pro les and differences at the single-cell resolution [23]. We collected three samples of fresh tongue tissue from patients diagnosed with primary and recurrent OSCC for this study.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a long way to go for the clinical translation of these laboratory findings. Single‐cell RNA sequencing (scRNA‐seq) and tissue microarray have proven beneficial for better understanding the heterogeneity and connections between metastatic lymph nodes and primary OSCC 108,109 . However, current research has not yet comprehensively and systematically elucidated the patterns of LNM occurrence and development in OSCC.…”
Section: Dilemmas and Prospectsmentioning
confidence: 99%